Pengaruh Good Corporate Governance Terhadap Manajemen Laba: Effect of good corporate governance on earnings management - Mohammad Irsyad, Fatih; Sundarta, M. Imam; Degita Aziz, Azolla (Yayasan Bina Internusa Mabarindo, 2023)
This study aims to determine the effect of good corporate governance on earnings management. either partially or simultaneously, good corporate governance referred to here are institutional ownership, independent commissioners and audit committees, while earnings management is calculated using discretionary accruals. This study uses a purposive sampling technique so that 11 food and baverage are listed on the Indonesia Stock Exchange for the period 2016-2018. The results of this study indicate that independent board of commissioners and audit commitees have no effect on earnings management because they have a significance value less than 0.05. Meanwhile, variabel institutional ownership has an effect on earnings management because the significance value is greater than 0.05. This is because large companies in preparing and reporting their financial conditions will be more careful and accurate, because the public tends to pay more attention to their performance. Meanwhile, the tendency of earnings management is carried out by smaller companies in order to show satisfactory performance results.